Contradiction of Waiver Clauses Articles 1266 and 1267 of the Civil Code in Standard Contracts - Latifa, Ratih; Badriyah, Siti Malikhatun (Universitas Wiralodra, 2023)
In a standard contract, one party can waive Articles 1266 and 1267 of the Civil Code. As a result, one of the parties will default or not fulfill the terms of the agreement, preventing the need for the deal to be annulled by a court and instead allowing it to be terminated by the parties themselves. However, in this case, there is a contradiction in the overriding clause of the article. In this research, we conducted a case study of rejecting overriding this clause in credit card agreements. The research results show that this article should not be excluded because it will result in reduced protection for both parties, and there is a need to balance the positions of both parties by upholding the principles of justice.